2020
DOI: 10.1002/zamm.202000117
|View full text |Cite
|
Sign up to set email alerts
|

Thence the moment of momentum

Abstract: Fifty years have passed since Truesdell's seminal paper on the origin and status of the balance for the moment of momentum was published in ZAMM. It is time to take stock: Important new developments in the theory of generalized continua with internal degrees of freedom and some fascinating fundamental applications need to be pointed out. Is there new evidence from classical papers regarding its independence from the balance of linear momentum? Can micropolar theory be used to “explain” electromagnetism? How is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…where q is the heat flux vector and r the specific radiation supply. It is the consequence of the principle that the total energy of the material body, i.e., the sum of kinetic energy in the form (4.8) and the internal energy, is conserved (see [26]). In order to obtain the formula (6.13) several algebraic manipulations are required after scalar multiplication of the balance of linear momentum (6.9) with v and the balance for the spin inertia tensor (6.10) by ν.…”
Section: Balances Of 3m Theoriesmentioning
confidence: 99%
“…where q is the heat flux vector and r the specific radiation supply. It is the consequence of the principle that the total energy of the material body, i.e., the sum of kinetic energy in the form (4.8) and the internal energy, is conserved (see [26]). In order to obtain the formula (6.13) several algebraic manipulations are required after scalar multiplication of the balance of linear momentum (6.9) with v and the balance for the spin inertia tensor (6.10) by ν.…”
Section: Balances Of 3m Theoriesmentioning
confidence: 99%
“…In particular, it is shown that the distinction between macroscopic angular momentum and moment of momentum, argued masterfully in [27], albeit with only a general allusion to directed media, is a natural implication of the homogenization theory. In fact, it is rigorously confirmed that couple forces, defined in terms of the microscopic state, enter in a non-trivial statement of macroscopic angular momentum balance [28,29]. The proposed theory differs from the micromorphic theory [3033] both methodologically and philosophically.…”
Section: Introductionmentioning
confidence: 98%
“…For metamaterials and their description, the scientific scrutiny is still ongoing [7,41,67]. The use of homogenization techniques for metamaterials is under development as well [56,66].…”
Section: Introductionmentioning
confidence: 99%